1995
DOI: 10.1002/arch.940300102
|View full text |Cite
|
Sign up to set email alerts
|

Chemical basis of differential oviposition by lepidopterous insects

Abstract: Phytochemical mediators serving as attractants, repellents, stimulants, or deterrents in oviposition behavior of moths and butterflies are reviewed in regard to the chemical mechanism of host selection. Ovipositing females seem generally to utilize plant volatiles as cues for orientation to host plants, and the subsequent contact evaluation of plants by means of less-or non-volatile secondary metabolites i s usually of great significance in host recognition. Most lepidopterans appear to be induced to oviposit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
85
1
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 142 publications
1
85
1
3
Order By: Relevance
“…Allyl isothiocyanate is a compound that plays a role in attracting female imago C. pavonana to lay eggs (Honda, 1995). An Oviposition Deterrent Index value (IPO) started from 0:12 to 0.95.…”
Section: Stem Bark Extract Bioactivity Of Odorata Lour Aglaia (Meliacmentioning
confidence: 99%
See 1 more Smart Citation
“…Allyl isothiocyanate is a compound that plays a role in attracting female imago C. pavonana to lay eggs (Honda, 1995). An Oviposition Deterrent Index value (IPO) started from 0:12 to 0.95.…”
Section: Stem Bark Extract Bioactivity Of Odorata Lour Aglaia (Meliacmentioning
confidence: 99%
“…The deterrent of laying eggs of C. pavonana might be caused by deterring components contained in the extract of A. odorata which is terpenoid class compound that can overcome the influence of stimulants found in broccoli plants. The attraction of female insects to lay eggs is a combination of responses to stimuli received by the senses of sight, mechanical, olfactory, and gustatory (Honda, 1995).…”
Section: Stem Bark Extract Bioactivity Of Odorata Lour Aglaia (Meliacmentioning
confidence: 99%
“…Of these compounds, the chemicals of the Papilionidae family have been widely studied. Especially many secondary metabolites (Renwick et al, 1994;Honda, 1995Honda, , 2005Honda and Nishida, 1999;Chachin et al, 2007), which often play an important role in the assessment of a plant as oviposition stimulant (Nishida, 2005;Ono et al, 2004) and feeding stimulant including amino acid derivatives, sugar-related acids, alkaloids, fl avonoids, and hydroxycinnamic acid derivatives (Nakayama et al, 2003), were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Because plants have evolved a wide array of toxic chemical defenses against 5 herbivores, the mechanism underlying host choice is expected to be highly related to the 6 plant chemical composition (Honda, 1995;Jaenike, 1990). The ability to discriminate 7 among plant chemical patterns varies depending on the degree of specialization (Janz and 8…”
Section: Introductionmentioning
confidence: 99%
“…The role of volatiles as oviposition deterrents has been described for many plant-6 insect systems (Gershenzon and Croteau, 1991;Renwick and Chew, 1994;Honda, 1995 …”
mentioning
confidence: 99%